Storytelling and Bulletin Board for Character Education - linda mayasari (Tell : Teaching of English Language and Literature Journal, 2013)
Indonesian minister of education attemps to raise up an issue about developing character education amongst indonesian schools based on the goal of Indonesia’s national education law No.20Year 2003. Adeyemi(2009) justifies that the concept of teaching character education should not be seen as the prerogative of subject alone. It should be taught integrated through any subject such as mathematics, science, humanities, social sciences, civic, sports, and so on, and in this case language, foreign language, national language, or even local language. The two ideas promoted here relating to build character in students are storytelling and bulletin board. Those can be employed by teacher in establishing language class; in addition, inserting other pertinent subjects to the material is possible to do.